El nacimiento de la Filosofía del derecho. De la Philosophia iuris a la Rechtsphilosophie - Ramis Barceló, Rafael (Historia del Derecho, 2021)
This book, according to the method of Begriffsgeschichte, explains the history of the notion of "Philosophy of Law". Starting from the distinction between the "simulata" and the "vera philosophia", the historical development continues with the Renaissance notion of "philosophia legalis" and shows that, from 1650 to 1730, treatises and manuals entitled "philosophia iuris" began to proliferate in Lutheran regions. These works (from Chopius until Reftelius, through Thomasius) had never been systematically studied. Starting from the Three-Year Course of Bachelor of Arts and from the Chair of "Natural Law", these professors looked for some first Principles of Law and wished to establish a conceptual basis for the pedagogical transition from the Faculty of Arts and Philosophy to the Faculty of Law. After a few decades in which the notion of "ius naturale et gentium" was definitively imposed (1730-1780), because of Kant's Philosophy there was a violent reaction against the philosophical "excesses" of rationalist Natural Law. Then Hugo and others coined the notion of "Philosophie des positiven Rechts", to which some philosophers like Hegel responded with their "Philosophie des Rechts" or "Rechtsphilosophie". Through this historical study, some reflections on the current dichotomy between "Theory" and "Philosophy of Law" are made and, according to the historical analysis, some solutions are proposed.---Este libro, siguiendo el método de la historia conceptual, explica la historia de la noción de "filosofía del derecho". Parte desde la distinción entre la "simulata" y la "vera philosophia", continúa con la noción renacentista de "philosophia legalis" y muestra que, desde 1650 hasta 1730, empezaron a proliferar, en las regiones luteranas, tratados y manuales con el nombre de "philosophia iuris". Estas obras (desde Chopius a Reftelius, pasando por Thomasius) jamás se habían estudiado sistemáticamente. Estos profesores, a partir del bachillerato trienal en Filosofía y de la cátedra de "derecho natural", buscaban unos primeros principios del derecho y querían trazar una base conceptual para la transición pedagógica desde la Facultad de Artes y Filosofía a la de Derecho. Tras unas décadas en las que se impuso definitivamente la noción de "ius naturale et gentium" (1730-1780), hubo -a causa de la filosofía kantiana- una violenta reacción contra los excesos filosóficos del iusnaturalismo racionalista. Se acuñó entonces -por parte de Hugo y otros- la noción de "Philosophie des positiven Rechts", frente a la cual algunos filósofos como Hegel respondieron con una "Philosophie des Rechts" o "Rechtsphilosophie". A través de este estudio histórico se llegan a unas reflexiones sobre la actual dicotomía entre "teoría" y "filosofía del derecho" y, a partir del análisis historico, se proponen algunas soluciones.